Penentuan Derajat Optimum Interpolasi pada Metode Lagrange dan Metode Newton Gregory dalam Mengestimasi Kasus Pasien Sembuh dari Covid-19 di Indonesia - Muhammad Julian; Lukita Ambarwati; Yudi Mahatma (Program Studi Matematika Universitas Negeri Jakarta, 2022)
Estimation is one method for approximation. The estimation method is the polynomial interpolation. Once of polynomial interpolation are Lagrange method and Newton Gregory method. In several references, the degrees of interpolation which is used on the Lagrange method or Newton Gregory method depends on the numbers of data. This paper was created to knowing the optimum degrees to interpolate 61 numbers of data. In this paper, points are determined to interpolate so that formed intervals of equal length. As for the degrees to be tested, namely degrees 2,4,5,10, and 20. Based on MAPE and MSE values for degree 2 are lower than degrees 4,5,10 and 20 in both methods so that the interpolation of the Lagrange and Newton Gregory degrees 2 is better than degrees 4,5,10, and 20.